CO2 conversion to CH4 using Zero Valent Iron (ZVI) and anaerobic granular sludge: Optimum batch conditions and microbial pathways - Vyrides, Ioannis; Andronikou, Maria; Kyprianou, Anthi; Modic, Anja; Filippeti, Andria; Yiakoumis, Christos; Samanides, Charis G. (My University, 2018)
This study investigates a new approach for carbon dioxide (CO2) conversion to methane (CH4) by using Zero Valent Iron (ZVI) and anaerobic granular sludge under aquatic mild conditions. Numerous studies have used ZVI to stimulate the anaerobic digestion of waste and wastewater. Up to date however, little research has been done on the use of ZVI and anaerobic granular sludge for the conversion of CO2 as a sole carbon substrate to CH4. The results showed that 75 g L-1 ZVI, 2 gVS L-1 anaerobic granular sludge at initial pH of 6 under daily pH regulation contributed to substantial CH4 production. It was pointed out that the initial ZVI (50 g L-1), with anaerobic granular sludge, was sufficient for the production of the same amount of CH4 over 2 CO2 re-feedings for a total of 67 days. To identify the microbial pathways for CO2 conversion to CH4, the following inhibitors were independently added: antibiotics for bacteria inhibition, 2-Bromoethanesulphonate (BES) for methanogens inhibition and Trichloromethane (CHCl3) for inhibition of bacteria and methanogens. Results showed that when antibiotics were added, they did not have any negative effect on CO2 conversion to CH4. This demonstrates that CO2 is converted to CH4 mainly through hydrogenotrophic methanogens and the contribution of homoacetogens was minor. Under these conditions of anaerobic granular sludge and ZVI the addition of BES and CHCl3 resulted in a high generation of H2, no production of CH4 and generation of 1110 mg L-1 and 730 mg L-1 in 8 days respectively.
Keywords: Anaerobic granular sludge; CO2 utilization; Homoacetogenesis; Hydrogenotrophic methanogens; Methane; Zero valent iron